Changes in the Accommodation-convergence Relationship after the Artisan Phakic Intraocular Lens Implantation for Myopic Patients - Ryu, Ik Hee; Han, Jinu; Lee, Hyung Keun; Kim, Jin Kook; Han, Sueng-Han (Korean journal of ophthalmology, 2014)
To evaluate the change of accommodation-convergence parameters after implantation of Artisan phakic intraocular lens (PIOL). Prospective study for the patients with the Artisan PIOL implantation was performed. A total of 37 patients (3 males and 34 females) enrolled the study. Preoperatively, convergence amplitude, the stimulus accommodative convergence per unit of accommodation (AC/A) ratio and the near point of convergence (NPC) were evaluated. After the Artisan PIOL implantation, the identical evaluations were repeated at 1 week, 1, 3, and 6 months after the surgery. Mean age was 24.3 ± 4.8 years old, and preoperative refractive error was -8.92 ± 4.13 diopters (D). After the implantation, mean refractive errors significantly decreased to within ±1.00 D, and noticeable complications were not found. The convergence amplitude and the stimulus AC/A ratio increased 1 month after the surgery, but progressively stabilized afterward to near preoperative values. NPC didn't show any significant change over follow-up period up to 6 months. These results regarding implantation of the Artisan PIOL revealed the increase of accommodation-convergence relationship within first 1 month after the surgery, but progressive stabilization was noted during follow-up periods.